The Effect of Water-Soluble Stem Extract “Kayu Kuning“ (Arcangelisia flava L.Merr) On The Growth Inhibition of Candida albicans ATCC 10231 and Trichophyton mentagrophytes IN VITRO - Rini Setyowati; Sudarsono Sudarsono; Setyowati E P (Biology, Medicine, & Natural Product Chemistry, 2014)
“Kayu kuning” (Arcangelisia flava L.Merr) was used when someone has a skin problem caused by Candida albicans and Trichophyton mentagrophytes. Scientific based medicine on this traditional knowledge was necessary be  done. Stem powderwas extracted by  distilled water.The extract was then evaporated. Qualitative and quantitative analysis of the active substance e.g., Berberin chloride by Thin Layer Chromatography (TLC)  The antifungal activity againts Candida albicans and Trichophyton mentagrophyteswere tested by using agar diffusion and microdilution methods.  The absorbance from microdilution were analized by One way ANOVA. The conclusion showed that the extract contained 1.55±0.12% w/walkaloid calculated as Berberine chloride. The inhibition zone for Candida albicans and Trichophyton mentagrophytes were 16.65±4.52 and 6.55±0.05 mm respectively. The MIC vallue for both fungi was 10 mg/mL.The MBC value for Candida albicans was 40 mg/mL and for Trichophyton mentagrophytes was 50 mg/mL. From the analysis with one-way ANOVA, shows that there are significant differences between the positive control group and the test solution with the negative control group with p=0.020 for Candida albicans and p=0.028 for Trichophyton mentagrophytes (p<0.050). Post hoc Tukey analysis results showed  that both inter-group and between the concentration of the test solution to the control group did not differ significantly positive because the value of p>0.050.